Implementation Of Digital-Based Management In Improving The Quality Of Academic Services At SDN 2 Bulukarto - Eli hafifah; Khulusiyyah Khulusiyyah; Muhtarom Muhtarom (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to analyze the implementation of digital-based management in improving the quality of academic services at SDN 2 Bulukarto. The research employed a descriptive qualitative approach involving the principal, teachers, and administrative staff as research subjects. Data were collected through observation, in-depth interviews, and documentation, while data analysis was conducted using data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings indicate that the implementation of digital-based management has improved the efficiency of academic services, enhanced data accuracy and transparency, and increased stakeholder satisfaction within the school community. Digital management processes covering planning, implementation, monitoring, and evaluation were found to be more systematic and integrated. Supporting factors include strong leadership commitment, availability of digital systems, and an adaptive organizational culture, while inhibiting factors involve limited digital competencies among some human resources and inadequate ICT infrastructure. The study concludes that digital-based management plays a strategic role in improving the quality of academic services and should be continuously developed through strengthening human resources, infrastructure, and school organizational culture.